2019
DOI: 10.1177/1129729819854593
|View full text |Cite
|
Sign up to set email alerts
|

FemoSeal® vascular closure device for antegrade common femoral artery access: Safety and technical notes

Abstract: Purpose: To retrospectively assess the efficacy and safety of FemoSeal® vascular closure device to achieve hemostasis following antegrade common femoral artery puncture after lower limb revascularization using vascular sheaths from 5 to 8 Fr. Methods: We reviewed the hemostatic outcome achieved with FemoSeal in 103 consecutive patients (mean age: 69 ± 8 years, 71 males) that undergone to 111 antegrade common femoral artery accesses for percutaneous lower limbs revascularization using 5- to 8-Fr vascular sheath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…After peripheral interventions, another study showed a success rate of the occlusion system independent of calcification [ 13 ]. Even after antegrade application of the FemoSeal system, calcification was not a predictor of complications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…After peripheral interventions, another study showed a success rate of the occlusion system independent of calcification [ 13 ]. Even after antegrade application of the FemoSeal system, calcification was not a predictor of complications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%